2008
DOI: 10.1080/10426500801901046
|View full text |Cite
|
Sign up to set email alerts
|

Correlating the GPx Activity of Selenocystine Derivatives with One-Electron Redox Reactions

Abstract: With an aim to develop water soluble, less toxic glutathione peroxidase (GPx) mimics, three selenocystine (SeCys) derivatives, viz., selenocystamine (SeA), diselenodipropionic acid (SeP), and methyl ester of diselenodipropionic acid (MeSeP) have been synthesized and examined for GPx activity along with SeCys. The GPx activity of the compounds was found to be in the order SeCys ∼ = SeA > MeSeP > SeP. The relative affinity of these GPx mimics towards the substrates thiol and hydroperoxide were determined by Line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…Conversely, the lowest activity for 5 would be due to the ionization of the amino groups to NH 3 + , which should decrease the oxidizability of the selenium atom. [11] The order of the catalytic activity strongly suggested that the GPxlike activities of selenides in water can be controlled by the electronic effects from the terminal hydrophilic substituents as well as the steric environments around the selenium atom. Second, the catalytic activity of 1 was investigated by using a dithiol, that is, dithiothreitol (DTT red ), instead of a monothiol substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, the lowest activity for 5 would be due to the ionization of the amino groups to NH 3 + , which should decrease the oxidizability of the selenium atom. [11] The order of the catalytic activity strongly suggested that the GPxlike activities of selenides in water can be controlled by the electronic effects from the terminal hydrophilic substituents as well as the steric environments around the selenium atom. Second, the catalytic activity of 1 was investigated by using a dithiol, that is, dithiothreitol (DTT red ), instead of a monothiol substrate.…”
Section: Resultsmentioning
confidence: 99%
“…5) [255]. The GPx activity of other selenocompounds without seleniumnitrogen bonds has also been investigated [202,256]. In one study, selenocystine and selenocystamine both had relatively similar GPx activity; however, 3,3-diselenobispropionic acid had GPx activity 25-29 times lower than [256].…”
Section: Glutathione Peroxidase Activity Of Selenium Compoundsmentioning
confidence: 98%
“…GPx activity measurement is a typical method used to determine selenium antioxidant activity, and a great deal of research has focused on the development of more potent GPx mimics, including small organoselenium compounds. [55][56][57][58][59][60] The selenium drug ebselen (2-phenyl-1,2-benzisoselazol-3(2H)-one) protects against ischemic brain injury in human clinical trials, 61 and prevents neurotoxicity in Parkinson's disease, a disease where ROS are considered the primary cause of pathogenesis. [61][62][63][64] The mechanism for this protective ability is thought to be reducing oxidative damage by H 2 O 2 in a manner similar to that of the GPx enzyme, and ebselen is typically used as the standard relative to which all selenium GPx measurements are compared.…”
Section: Glutathione Peroxidase Activity Of Selenium Compoundsmentioning
confidence: 99%